A survey of literature on selection of third party logistics service provider. (26th October 2010) - Rajesh, R.; Pugazhendhi, S.; Ganesh, K.
The outsourcing of logistics activities has become a common practice by many companies, and over the last two decades, the third party logistics (3PL) service providers have become important players in many supply chains and industries because they take part in the cost reduction, the productivity profits and the improvement of the service quality of their customers. 3PL plays a key role in the logistic activities between the outsourcing company, the marketplace, and the customers, which implies the need for an efficient choice of the 3PL service providers. 3PL service provider selection has gained great attention in logistics management literature. Based on a comprehensive literature review, a classification framework is proposed in this paper. Altogether 46 refereed academic journal articles are reviewed and classified. Based on the review of the papers some new research settings are suggested.